Answer:
[tex](x+3)(x-8)=0[/tex]
Step-by-step explanation:
First, write out the equation as it is given in the problem:
[tex]x^{2}-5x-24=0[/tex]
Now, you have to split up the "-5x" to get to factored form. The way to do this is to look for the factors of "a" times "c" that sum to "b":
So, in this problem, a=1, b=-5, and c=-24. So, find the factors of (1*-24) that sum to (-5). To clarify, (1*-24)=-24, so you have to find factorsof -24 that sum to -5.
Let's write out a list of factors.
[tex]1,-24---1+-24=-23no\\-1,24---1+24=23no\\2,-12---2+-12=-10no\\-2,12----2+12=10no\\3,-8---3+-8=-5yes[/tex]
Therefore, our two factors will be 3x and -8x.
Now, let's rewrite our equation with these new factors in place of the -5x:
[tex]x^{2}-5x-24=0\\x^{2}+3x-8x-24=0[/tex]
Next, find your factored expressions:
[tex]x^{2}+3x-8x-24=0\\(x^{2}+3x)(-8x-24)=0\\[/tex]
Take the GCF from each set of parenthesis:
[tex]x(x+3)-8(x+3)=0[/tex]
The GCFs that you took out will become your second in the set for factorde form. It will be written as "x-8".
Therefore, your equation in factored form will be:
[tex](x+3)(x-8)=0[/tex]